1977
DOI: 10.2134/jeq1977.00472425000600040016x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Accumulation in Plants and Animals of Polluted and Nonpolluted Grasslands

Abstract: Cadmium concentrations in soils, plants, and animals from two sites in southwestern Montana were determined. Primary emphasis was placed upon agriculturally important plants and animals. One of the sites had a history of pollution from a smelter complex, while the second had no history of industrial contamination.Determination of extractable Cd in soils collected at intervals along a line from the smelter to the polluted study site showed that this smelter was probably the source of the high soil Cd levels. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Industrial emission, animal manures, sewage sludge and phosphate fertilizers are reported to have increased Cd concentrations in agricultural soils (Rao and Kashifuddin 2012). Munshower (1977), for example, reported high Cd levels (29 mg/kg) in Montana up to two km northeast of a Pb-Zn smelter, which decreased with distance and reached near background levels after 24 km. Recently, Shahid et al (2013b) reported high levels of Cd (70.2 mg/kg) within a 40 km 2 area surrounding the Metaleurop smelter near Evin-Malmaison (North of France).…”
Section: Level and Sources In Soilmentioning
confidence: 99%
“…Industrial emission, animal manures, sewage sludge and phosphate fertilizers are reported to have increased Cd concentrations in agricultural soils (Rao and Kashifuddin 2012). Munshower (1977), for example, reported high Cd levels (29 mg/kg) in Montana up to two km northeast of a Pb-Zn smelter, which decreased with distance and reached near background levels after 24 km. Recently, Shahid et al (2013b) reported high levels of Cd (70.2 mg/kg) within a 40 km 2 area surrounding the Metaleurop smelter near Evin-Malmaison (North of France).…”
Section: Level and Sources In Soilmentioning
confidence: 99%
“…In the Uni ted States, in Deer Lodge Valley, Montana average Cd concentrations in contaminated (from smelting) vs. noncontaminated areas were: grasses, 1.72 and 0.07; alfalfa, 0.83 and 0.06; and barley grain, 0.65 and 0.08 ppm, respectively (Munshower, 1977). Average levels in animal tissues were: cattle liver, 0.34 and 0.06; cattle kidney, 1.67 and 0.22; swine liver, 0.24 and 0.14; and swine kidney, 0.99 and 0.39 ppm, from contaminated and noncontaminated areas, respectively.…”
Section: Atmospheric Depositionmentioning
confidence: 99%
“…However, topsoil metal concentrations are generally found to be at maximum levels in the immediate smelter area with an exponential decrease to near background concentrations over relatively small distances (John, 1971;Wang et al, 1992;Munshower, 1977;Burkitt et al, 1972;Roberts et al, 1974;Lagerwerff et al, 1973;Landrigan et al, 1975;Farago and O'Connell, 1983;Linzon et al, 1976;Keizer et al, 1982;Schmitt et al, 1979). The extent of this rapid fall-off range varies between different studies but is often less than 2-3 km.…”
Section: Contamination Of the External Environment In Smelter Areasmentioning
confidence: 99%